2006
DOI: 10.1007/s00520-006-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in palliative radiation therapy: reframing hope in caregivers and patients with brain metastases

Abstract: Given the importance of caregivers in the care of patients with brain metastases, fulfilling their unique informational needs appears to require more attention. The blurred boundary between hopes and expectations for WBRT creates unique challenges in joint treatment decision making for patients with brain metastases and their caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 36 publications
0
47
0
5
Order By: Relevance
“…It can be challenging to recommend supportive care alone to patients, especially when they come to the RRRP expecting WBRT. A qualitative study found the major factors influencing patients and caregivers in decision making for WBRT were hope, knowledge, expectations of radiotherapy, and current symptoms (21). Oncologists find it difficult to discuss treatment options at the end of life and have admitted to delivering treatment not likely to help to maintain patient hope (22).…”
Section: Discussionmentioning
confidence: 99%
“…It can be challenging to recommend supportive care alone to patients, especially when they come to the RRRP expecting WBRT. A qualitative study found the major factors influencing patients and caregivers in decision making for WBRT were hope, knowledge, expectations of radiotherapy, and current symptoms (21). Oncologists find it difficult to discuss treatment options at the end of life and have admitted to delivering treatment not likely to help to maintain patient hope (22).…”
Section: Discussionmentioning
confidence: 99%
“…Patients may also know of family members or friends who have died of cancer after a similar treatment scheme as they are receiving themselves, and now, the patients hope for quality of life goals that they once saw as important for a loved one. Sze et al [24], in their study of brain tumour patients, found that patients' hopes fell into the categories cure, increased life expectancy, improved symptom control, and improved acceptance. As shown in Fig.…”
Section: Direction Of Hopementioning
confidence: 97%
“…Although the facts regarding an advanced cancer are difficult to accept, patients and caregivers still desire information 14,20 . However, the information needs of patients and caregivers vary.…”
Section: Discussionmentioning
confidence: 99%
“…Patients generally focus on current information needs; caregivers want more information about the future (for example, life expectancy and anticipated symptoms) 14 . The responsibility of health care providers and patient educators is to present the information in a sensitive manner that equips patients and caregivers alike with the necessary knowledge and that realigns hope against realistic expectations to facilitate successful coping with the diagnosis 14 . Traditionally, written patient information has been presented in pamphlets, booklets, and brochures that use a fact-based approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation